Valuation of supporting angle inside raft foundation of BRAC University new campus project (variation order #018) - BUCG-ABC Joint Venture (BUCG-ABC JV) (Brac University, 2023)
This record consists of general correspondence regarding valuation of supporting angle inside raft foundation of BRAC University new campus project (variation order #018).